The impact of service quality on organizational performance. Does market orientation matter? - Liew, Sin Yean. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study tries to examine the relationship between service quality and market orientation and their impact towards organizational per formance. A total of 175 sets of questionnaires were distributed to the employees of the selected organizations in Kuching, and 92% of it, which is 161, was returned. The results show that service quality has a significant effect on organizational performa nce and market orientation. Market orientation also has a significant effect on organizational performance. In addition, this study found that market orientation will moderate the relationship between service quality and organizational performance. There i s still a shortage of research studying the impact of market orientation as a moderator on the relationship between service quality and organizational performance. Thus, this study contributes a significant knowledge to the service industry.